Interfejs marketingowo-finansowy w analizach portfelowych wspomagających strategie marketingowe - Golik-Górecka, Grażyna (The finance-marketing interface and portfolio analyses supporting marketing strategies, 2008)
The subject of the article is the problem of theoretical and practical aspects of marketing costs. The article includes the analyses of costs presentation in economy, accounting and finance literature. The concept of marketing costs is presented on background of general cost consideration. The identification of these costs is a very complex process because of the nature of marketing system. Empirical studies presented in this article enabled the identification of the marketing costs categories spontaneously indicated by marketing and finance managers of enterprises in Poland. The results of research enabled also the verification of marketing costs registration and identification of managers attitudes towards methods of cost classification used in firms.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 42-54